KAPANG ENDOFIT DARI TAMAN NASIONAL GUNUNG HALIMUN SEBAGAI PENGHAMBAT PERTUMBUHAN MIKROBA PATOGEN Salmonella thypi DAN Candida albicans - Ruth Melliawati; Puspita Suci Wulandari (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Endophytic fungi live inside plants without harming the host. The purpose of this research was to screen endophytic fungi which could inhibit Salmonella thypi and Candida albicans, as well as characterizing of endophytic fungi, and antimicrobial compound produced by endophytic fungi. Some methods were used on this research. Diffusion agar plate methode was used to screen endophytic fungi which could produce antimicrobial compound against Salmonella thypi and Candida albicans. Standard plate count was used to measure fungi growth. Antimicrobial compound produced by endophytic fungi was analized by TLC and HPLC technique, compared with standard antibiotic, chloramphenicol and nystatin. The result showed 5 kinds of endophytic fungi produced antimicrobial compounds against Salmonella thypi. The largest zone of inhibition was 115 mm2 shown by Hl.25F.112. Two kinds of endophytic fungi were able to inhibit Candida albicans with the largest inhibiting zone was 164 mm2 shown by Hl.108F.481. The morphology of Hl.108F.481 indicated that this fungus had vertical hypha with sporangium at the end of the hypha and Hl.25F.112 had partioned hypha and oval-shape ascus. TLC and HPLC analysis showed that water extract of Hl.25F.112 (1s), chloroform extract of Hl.25F.112 (1c) and chloroform extract of Hl.108F.481 (2c) contained anti-microbial compound with retention time (RT) closed to chloramphenicol and water phase of Hl.25F.112 (1s) closed to nystatin.